Advancing Decision-Visualization Environments—Empirically informed Design Recommendations. (October 2020) - John, Beatrice; Lang, Daniel J.; von Wehrden, Henrik; John, Ruediger; Wiek, Arnim
Highlights: Decision-visualization facilities, compared across more than 50 attributes, share similar experiences, practices, and challenges. The study offers empirically informed recommendations to advance decision-visualization environments. Advancements focus on adaptive infrastructure and transformative human-computer interaction. DVEs effectively provide settings for exploration and experimentation, rather than only explanation approaches. An active network of DVEs could constitute a productive learning community. Abstract: Semi-immersive visualization facilities support research, planning, and decision-making at the science-society-policy interface. Decision theaters, visualization studios, and similar installations—here referred to as Decision-Visualization Environments (DVEs)—facilitate human-computer-content interactions to explore climate change impacts, resource management practices, and urban design solutions. This comparative study analyzes the current practices of seven DVE facilities from around the world based on expert interviews, site visits, and document review. We found common practices across 53 attributes concerning the planning, stakeholder involvement, and realization of DVE activities. DVEs need good facilitation and purposeful combination to unlock their full potential. An active network of DVEs could constitute a productive learning community to pool and coordinate activities and share insights. Based on our findings, we deduce recommendations on how to improve the design of existing DVEs, to create new DVEs, as well as to plan DVE projects and events.